Impacts of Firms’ Internal Information Environment on Tax Avoidance (Case Study: Companies Listed In Tehran’s Stock Exchange) - Ghafoori, Jahanbakhsh (2017)
The main purpose of this study is to investigate the impacts of firms’ internal information environment on tax avoidance. The research method includes a data panel and is generally of semi-experimental fashion. The population of research is consisted of the entire companies and firms listed in Tehran’s stock exchange as 496 firms from the beginning of 2007 until the end of financial year of 2014. Among the population, a number of 86 firms were selected as the sample through systematic omitting method. For the purpose of data analysis, the tests of T and multivariate linear regression were incorporated into the study. Results indicate that impact of quality of internal information on tax avoidance is higher in those companies in which information play a more important role. Firms which operate under geographic dispersion make more use of the quality of their internal information, because this information helps them towards reduced tax avoidance. High quality of internal information and commercial dispersion force these firms towards avoiding larger taxes. In addition, quality of internal information is not effective on firms which are under reconstruction status.